Performance of an instrumented slope covered by a capillary barrier system - Rahardjo, Harianto (2011)
A capillary barrier as a cover system is a two‐layer system of distinct hydraulic properties to prevent water infiltration into the underlying soil by utilizing unsaturated soil mechanics principles. This paper illustrates the application of the capillary barrier system on a slope which experienced shallow slip failures to prevent future rainfall‐induced slope failures. In this study, the capillary barrier system was designed as a cover system for residual soil slopes with a steep slope angle under heavy rainfall conditions of the tropics. The capillary barrier system was constructed using fine sand as the fine‐grained layer and granite chips as the coarse‐grained layer. Both layers were contained in cellular confinement system. The slope was instrumented with tensiometers and piezometers. The tensiometers were installed at different depths from about 0.5 m to 2.0 m below the slope surface. An adjacent original slope without the capillary barrier system was also instrumented using tensiometers in order to investigate the performance and effectiveness of the capillary barrier system in reducing rainwater infiltration and maintaining negative pore‐water pressure in the slope. The detailed installation of matric suction measurement device is discussed comprehensively in this paper. The measurement results showed that the capillary barrier system was effective in maintaining the negative pore‐water pressures during rainfalls, particularly on the crest of the slope.